2021
DOI: 10.1177/0022022120987620
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, Stress Reactivity, and Depressive Symptoms Among “Third Culture Kids” in the United Arab Emirates

Abstract: So called third culture kids (TCKs), the children and adolescents who accompany their parents on long-term overseas work assignments, often have to face life changes, cultural challenges and threats to social identity. The frequency, intensity and nature of these challenges arguably places some TCKs at heightened risk of stress-related mental health problems. Trait mindfulness, an attribute that can be enhanced through intervention, has been found to buffer against stress reactivity and common mental health pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Furthermore, individuals high in mindfulness could be more able to notice how the mind reacts to thoughts, sensations, and information, recognizing and avoiding habitual patterns that unconsciously guide behavior, thereby selecting better and healthier ways of responding to experiences. Indeed, some studies suggested that mindfulness buffers stressors’ impact on depressive symptoms among adolescents (Thomas et al, 2021 ). Similarly, considering that previous studies reported that mindfulness predicts a reduction in stressors in the long term among adolescents (Calvete et al, 2017 ), it could be that having fewer stressors reduces stress and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, individuals high in mindfulness could be more able to notice how the mind reacts to thoughts, sensations, and information, recognizing and avoiding habitual patterns that unconsciously guide behavior, thereby selecting better and healthier ways of responding to experiences. Indeed, some studies suggested that mindfulness buffers stressors’ impact on depressive symptoms among adolescents (Thomas et al, 2021 ). Similarly, considering that previous studies reported that mindfulness predicts a reduction in stressors in the long term among adolescents (Calvete et al, 2017 ), it could be that having fewer stressors reduces stress and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This is a particularly unique finding, since previous studies have highlighted a variety of negative outcomes of an international background (Davis et al. , 2013; Thomas et al. , 2021).…”
Section: Discussionmentioning
confidence: 51%
“…The participants' drive for international goals was based on their internationally developed selfefficacy and outcome expectations, since they described an expectation of positive outcomes to come from their international background. This is a particularly unique finding, since previous studies have highlighted a variety of negative outcomes of an international background (Davis et al, 2013;Thomas et al, 2021). Despite being children during their JGM 10,3 parents' expatriate assignments abroad, the data indicates that this time was in fact significant in influencing these individuals' future choices.…”
Section: Atck's Career Ambitionsmentioning
confidence: 60%
“…This is especially the case during the COVID-19 pandemic due to a recognized global lack of control over many aspects of life, including self-representation in educational spaces. Some 'stigmatized identity aspects' (Goffman, 1959) such as financial constraints, lack of a suitable study environment, technical difficulties, and mental health concerns, which are common among university-age students globally (Thomas et al, 2021), are more easily hidden on campus. As Smith et al (2021: 127) point out, 'the brick-and-mortar campus allows students with financial needs to mitigate those needs through campus resources, but access to many of these resources disappeared when campuses closed'.…”
Section: Discussionmentioning
confidence: 99%